Риторичні питання і риторичні твердження як елементи наративного коду інтимізації - Палійчук, Анна Леонардівна; Paliychuk, Anna (Запоріжжя: ЗНУ, 2010)
Стаття присвячена аналізу впливу риторичних питань та тверджень на інтимізацію наративу. The article is dedicated to the analysis of the influence of rhetorical questions and statements on the intimisation of the narrative.
Rhetorical Questions and Rhetorical Statements as Elements of the Intimisation Narrative Code
Keywords: наратив; риторичні питання; риторичні твердження; інтимізація; narrative; rhetorical questions; rhetorical statements; intimisation